Dieckol Isolated from Eisenia bicyclis Ameliorates Wrinkling and Improves Skin Hydration via MAPK/AP-1 and TGF-β/Smad Signaling Pathways in UVB-Irradiated Hairless Mice - Jae-Min Kim; Kyung-Sook Chung; Young-Seo Yoon; Seo-Yun Jang; So-Won Heo; Geonha Park; Young-Pyo Jang; Hye-Shin Ahn; Yu-Kyong Shin; Sun-Hee Lee; Kyung-Tae Lee (Marine Drugs, 2022)
Repetitive exposure to ultraviolet B (UVB) is one of the main causes of skin photoaging. We previously reported that dieckol isolated from Eisenia bicyclis extract has potential anti-photoaging effects in UVB-irradiated Hs68 cells. Here, we aimed to evaluate the anti-photoaging activity of dieckol in a UVB-irradiated hairless mouse model. In this study, hairless mice were exposed to UVB for eight weeks. At the same time, dieckol at two doses (5 or 10 mg/kg) was administered orally three times a week. We found that dieckol suppressed UVB-induced collagen degradation and matrix metalloproteinases (MMPs)-1, -3, and -9 expression by regulating transforming growth factor beta (TGF-β)/Smad2/3 and mitogen-activated protein kinases (MAPKs)/activator protein-1 (AP-1) signaling. In addition, dieckol rescued the production of hyaluronic acid (HA) and effectively restored the mRNA expression of hyaluronan synthase (HAS)-1/-2 and hyaluronidase (HYAL)-1/-2 in UVB-irradiated hairless mice. We observed a significant reduction in transepidermal water loss (TEWL), epidermal/dermal thickness, and wrinkle formation in hairless mice administered dieckol. Based on these results, we suggest that dieckol, due to its anti-photoaging role, may be used as a nutricosmetic ingredient for improving skin health.